HIDUP DALAM KOMUNITAS VIRTUAL: STUDI ETNOGRAFI PEREMPUAN BERTATO DI RUANG SIBER - Andreas, Rino; Akhyat Sulkhan, Khumaid; Rizki Rosidah, Dede; Yaqi, Yu (Universitas Hasanuddin, 2023)
This study aims to look at the construction of tattooed bodies in cyberspace and explain gender relations in the Indonesian Tattoo Women's (PTI) virtual community. This qualitative research uses a virtual ethnographic method that involves the participation of researchers in a community. As a result, the PTI community has a style of interaction that shapes culture in cyberspace. PTI is a place for tattoo lovers, both